2022
DOI: 10.1155/2022/8521922
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral Transplantation of Mesenchymal Stromal Cell Compounded with Recombinant Peptide Scaffold against Chronic Intracerebral Hemorrhage Model

Abstract: Background. Due to the lack of effective therapies, stem cell transplantation is an anticipated treatment for chronic intracerebral hemorrhage (ICH), and higher cell survival and engraftment are considered to be the key for recovery. Mesenchymal stromal cells (MSCs) compounded with recombinant human collagen type I scaffolds (CellSaics) have a higher potential for cell survival and engraftment compared with solo-MSCs, and we investigated the validity of intracerebral transplantation of CellSaic in a chronic IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Collagen gels loaded with BDNF neutralizing antibodies significantly reduced the formation of axon branches after facial nerve transection in rats without significant adverse effects on neuronal survival and axon elongation [44] .Rat cell Saics (rCellSaics) derived from bone marroe-derived MSC (rBMSCs) have a higher potential to secrete neurotrophic factors. Intracerebral transplantation of CellSaics is beneficial to neural recovery in chronic intracerebral hemorrhage models, and this effect can be reversed by BDNF neutralizing antibodies [45] . Our study suggests that the BDNF neutralizing antibody is a promising drug for the treatment of type I neurofibroma.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen gels loaded with BDNF neutralizing antibodies significantly reduced the formation of axon branches after facial nerve transection in rats without significant adverse effects on neuronal survival and axon elongation [44] .Rat cell Saics (rCellSaics) derived from bone marroe-derived MSC (rBMSCs) have a higher potential to secrete neurotrophic factors. Intracerebral transplantation of CellSaics is beneficial to neural recovery in chronic intracerebral hemorrhage models, and this effect can be reversed by BDNF neutralizing antibodies [45] . Our study suggests that the BDNF neutralizing antibody is a promising drug for the treatment of type I neurofibroma.…”
Section: Discussionmentioning
confidence: 99%
“…Takamiya et al 60 recently reported that MSCs compounded with a biodegradable scaffold (CellSaic) resulted in better functional recovery than MSCs alone in a chronic ICH model. CellSaic released higher amounts of trophic factors such as BDNF, HGF, vascular endothelial growth factor (VEGF), and GDNF; extracellular vesicles (exosome) were also released in CellSaic.…”
Section: Preclinical Studiesmentioning
confidence: 99%